2002
DOI: 10.4049/jimmunol.169.9.5181
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Mitochondrial Damage in Determining Outcome of Macrophage Infection with Mycobacterium tuberculosis

Abstract: Human macrophages (Mφ) respond to Mycobacterium tuberculosis (Mtb) infection by undergoing apoptosis, a cornerstone of effective antimycobacterial host defense. Virulent mycobacteria override this reaction by inducing necrosis leading to uncontrolled Mtb replication. Accordingly, Mφ death induced by inoculation with Mtb had the characteristics of apoptosis and necrosis and correlated with moderate increase of mitochondrial permeability transition (MPT), mitochondrial cytochrome c release, and caspase-9 and -3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 53 publications
1
60
0
Order By: Relevance
“…After release into the cytosol, cytochrome c forms a complex containing Apaf-1, ATP, and procaspase-9, resulting in the activation of downstream caspases (12) and apoptosis. Cytosolic cytochrome c also binds to inositol (1,4,5) triphosphate receptors of the endoplasmatic reticulum, amplifying the Ca 2ϩ release from the endoplasmatic reticulum (30) that causes mitochondrial Ca 2ϩ influx necessary for induction of apoptosis (31). In contrast to apoptosis, necrosis is a consequence of the opening of the MPT pore (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After release into the cytosol, cytochrome c forms a complex containing Apaf-1, ATP, and procaspase-9, resulting in the activation of downstream caspases (12) and apoptosis. Cytosolic cytochrome c also binds to inositol (1,4,5) triphosphate receptors of the endoplasmatic reticulum, amplifying the Ca 2ϩ release from the endoplasmatic reticulum (30) that causes mitochondrial Ca 2ϩ influx necessary for induction of apoptosis (31). In contrast to apoptosis, necrosis is a consequence of the opening of the MPT pore (32).…”
Section: Discussionmentioning
confidence: 99%
“…M were cultured at a density of 1.5 ϫ 10 6 mononuclear cells/2 ml/well in 6-well cluster plates (Corning Glass) (5). The cells were infected with H37Rv at an MOI of 10:1 for 6, 12, and 48 h, washed with ice-cold PBS, and treated with 50 g/ml digitonin in PBS in the presence of protease inhibitor mixture (Roche) for 5 min on ice.…”
Section: Assessment Of Cytochrome C Release From the Mitochondria By mentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium causes mitochondrial outer membrane permeabilization characterized by cytochrome c release from the mitochondrial inter-membrane space and apoptosis. Duan et al (2002) and Chen et al (2006) have reported that mycobacterial infection affects mitochondrial function. 22,23 There is consistent evidence for a central role of mitochondrial dysfunction in these pathologies.…”
Section: Classifying Modules Of the Tuberculosis And Hiv Co-infected mentioning
confidence: 99%
“…Duan et al (2002) and Chen et al (2006) have reported that mycobacterial infection affects mitochondrial function. 22,23 There is consistent evidence for a central role of mitochondrial dysfunction in these pathologies. 24 Nucleotide reverse transcriptase inhibitors (NRTIs) have been described to be primarily responsible for mitochondrial dysfunction in adipose tissue and liver.…”
Section: Classifying Modules Of the Tuberculosis And Hiv Co-infected mentioning
confidence: 99%